Artificial Intelligence and the Transformation of Digital Services in Islamic Banking: A Case Study of Bank Syariah Indonesia - Luqman Syakirunni’am; Zohaib Hassan Sain; Syauqie Muhammad Marier; Syukron Jamil (LogicLink, 2025)
Digital transformation in the Islamic banking sector is necessary in the era of technological disruption. However, implementing artificial intelligence (AI) still faces challenges, especially in non-metropolitan areas. This research aims to explore the role of AI in transforming digital services at Bank Syariah Indonesia (BSI) Semarang Branch, while emphasizing its compliance with maqashid Sharia principles. This research uses a phenomenological qualitative approach through in-depth interviews, participatory observation, and analysis of internal documentation of employees and customers. The main findings show that AI significantly improves service efficiency through digital onboarding, chatbot “Hasanah Assistant”, and a pattern-based automated transaction system. This innovation is considered to accelerate services while maintaining the principles of property protection (hifzh al-mal) and life (hifzh al-nafs). However, challenges arise regarding AI’s limited adaptation to local cultural contexts, senior employees’ resistance to digitalization, and customers’ limited digital literacy. This highlights the importance of a hybrid approach between technology and humanization of Islamic banking services. The uniqueness of this research lies in its focus on regional branches that have not been widely explored in the academic literature, as well as its contribution to expanding the understanding of AI as a strategic medium, not just an automation tool. The implications of this research emphasize the need for an efficient, ethical, and inclusive AI system design, oriented towards Islamic values. The research suggests a participatory digital transformation strategy that is adaptive to local values and consistent with maqashid Sharia to ensure the sustainability of technological innovation in Islamic banking.